DISSOLUTION PROFILE STUDIES FOR RAMIPRIL AND LERCANIDIPINE FIXED-DOSE COMBINATION - A. A. Shadrin; E. V. Flisyuk; I. E. Smekhova (Разработка и регистрация лекарственных средств)
This article describes the results of the development of composition and technology of a combined drug, containing lercanidipine and ramipril, affording equivalent dissolution kinetics with original drugs. The comparative release profiles of the active pharmaceutical ingredients are shown. The choice of a solid dosage form in the form of bi-layer tablets was substantiated.